1968
DOI: 10.1203/00006450-196811000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Sweat Composition in Relation to Rate of Sweating in Patients with Cystic Fibrosis of the Pancreas

Abstract: ExtractSingle sweat droplets were collected from a mineral oil-covered finger surface ( fig. 1). Rate of sweat production (sweat rate) per gland per hour was calculated. Using microtechniques, the concentrations of electrolytes and metabolites, osmolarity, pH, and viscosity were determined in undiluted pooled sweat. The following results were obtained:No significant difference was observed in sweat rate per gland between control subjects and patients with cystic fibrosis of the pancreas (CFP).Concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
1
1

Year Published

1971
1971
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 57 publications
9
53
1
1
Order By: Relevance
“…Previous studies (8) reported that lactate in the sweat from pooled secretions of single sweat glands obtained from a limited number of individuals ranged from 16 mM at high sweat rates to 40 mM at low sweat rates. We cannot explain the difference between the much lower lactate concentration that we found at low sweat rates or the opposite relationship between rate and concentration (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (8) reported that lactate in the sweat from pooled secretions of single sweat glands obtained from a limited number of individuals ranged from 16 mM at high sweat rates to 40 mM at low sweat rates. We cannot explain the difference between the much lower lactate concentration that we found at low sweat rates or the opposite relationship between rate and concentration (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…This quantitative increase in sweat electrolytes is the phenotypic change most consistently demonstrable in the CF patient. Because this finding is independent of the age or the clinical status of the patient (I, 10,29), the electrolyte abnormality appears to be a primary manifestation of the basic molecular defect underlying CF. There is no major morphologic alteration of the sweat gland (19).…”
Section: Speculationmentioning
confidence: 99%
“…The decrease in conductivity observed was not diagnostically signi®cant. Emrich et al 13 analysed sweat from single sweat glands stimulated to a different extent by total body heating, by local heating or by pilocarpine iontophoresis. Their results indicated a dependence of solute concentration on sweating rate, and this varied with the nature of the solute.…”
Section: Discussionmentioning
confidence: 99%